Disorders of carbohydrate metabolism and their relationship with the prevalence of cancer in patients with acromegaly – authors’ own observations - Malicka, Joanna Elżbieta; Kurowska, Maria; Dudzińska, Marta; Smoleń, Agata; Oszywa-Chabros, Anna; Tarach, Jerzy S. (Family Medicine & Primary Care Review, 2016)
Background . Acromegaly is a rare chronic disease with an excessive secretion of growth hormone, which leads to characteristic changes in appearance, organ and metabolic complications and neoplasms, which are a significant cause of shortened survival time. One of the most common consequences of acromegaly is disturbed carbohydrate metabolism. Objectives . The aim of this study was to assess the prevalence of disorders of carbohydrate tolerance and their relationship with the prevalence of malignant tumours in subjects with acromegaly. Material and methods. The study group comprised 69 patients with confirmed acromegaly (26 M, 43 F), aged 26–83 (mean 58.9 ± 11.0). Medical histories and the results of laboratory tests – plasma fasting glucose and oral glucose tolerance test, as well as the results of imaging and histopathological examinations performed in cases of suspected cancer lesions were analyzed. Results Disorders of carbohydrate tolerance were confirmed in a total of 46 patients (66.7%). 23 patients (33.3%) had normal glucose tolerance. Diabetes was diagnosed in 22 patients (31.9%), while prediabetes was diagnosed in 24 (34.8%) patients. In the analyzed group there were 6 cases of cancers, including 5 patients with concomitant diabetes, which represented a value significantly higher (p = 0.01) compared to patients without diabetes. The sixth case of cancer was detected in a woman with IGT . In patients with normal glucose tolerance there was no case of cancer. Conclusions . Among patients with acromegaly, disorders of carbohydrate tolerance occur in more than half of the cases, which confirms the need for active screening in this group of patients, in which a significant role is played by General Practitioners. General Practitioners should also consider the possibility of acromegaly in the differential diagnosis of glucose tolerance disorders detected in their patients. All patients with acromegaly, especially with concomitant diabetes or prediabetes, should be screened for cancers.